Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
The zeros are -6 and -2
Step-by-step explanation:
factor the equation.
(x+2)*(x+6)
x+2=0
x+6=0
x
2
+
8
x
+
12
=
0
Step 1: Factor left side of equation.
(
x
+
2
)
(
x
+
6
)
=
0
Step 2: Set factors equal to 0.
x
+
2
=
0
or
x
+
6
=
0
x
=
−
2
or
x
=
−
6
X=-2 or x=-6
2
+
8
x
+
12
=
0
Step 1: Factor left side of equation.
(
x
+
2
)
(
x
+
6
)
=
0
Step 2: Set factors equal to 0.
x
+
2
=
0
or
x
+
6
=
0
x
=
−
2
or
x
=
−
6
X=-2 or x=-6
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.